Microbiological and antibiotic sensitivity pattern of surgical site infection following caesarean section in a tertiary care center of Chhattisgarh - Thakur, Neha; Kujur, Avinashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: It is one of the most common surgery practiced in present era in obstetric population it has led to rise in postoperative morbidity in the form of surgical site infection (SSI). It not only burdens the health system but it also puts a serious negative impact on patient’s life. The present study is aimed to determine the incidence, risk factors and the microbiological and antibiotic sensitivity pattern for SSI following caesarean section in our institute. Methods: The study is prospective, descriptive study carried out in department of obstetrics and gynecology of Pt. Jawaharlal Nehru medical college, Raipur between May 2019 and April 2020. Results: Out of the 1215 participants who underwent caesarean section, 251 patients had SSI, with incidence of 20.6% among them superficial SSI (n=154) was 61.3% while deep SSI (n=75) 29.8% and 8.7% (n=22) organ/space SSI. Gram positive organism was highest isolated from superficial SSI 66.2% while from deep SSI and organ/space SSI gram positive organism isolated was 45.2% and 54.2% respectively, gram negative organisms were maximum isolated from organ/space SSI 40.9%followed by deep and superficial SSI 36% and 34.4% respectively. Most isolates were highly resistant to cephalosporins, gentamycin and amoxicillin; moderately resistant to fluoroquinolones and highly sensitive to vancomycin, carbapenem and linezolid. Conclusions: Our tertiary centre had post caesarean SSI rate of 20.6% which was high. By analyzing the microbiological and sensitivity pattern we can use evidenced-based sensitive antibiotics to be commenced initially when wound infection is identified in our wards while awaiting the result of wound swab microscopy, culture and sensitivity (48-72 hours), to individualize our antibiotic prophylaxis and postoperative antibiotic protocol policy to reduce the further complications.